After-effects of a closed copper mine: detailed analysis of environmental impacts in soil and plant samples - Konanç, Mustafa Umut; Yavuz, Emine; Kariper, İshak Afşin; Değermenci, Gökçe Didar (Springer Science and Business Media LLC, 2024)
AbstractIn several countries around the world, abandoned mining sites are blighted by pollution from metal and metalloids. Generated by mining processes, toxic pollutants have lasting effects on the ecosystem. The study examined the environmental impact of waste from a copper mine that was operated by the Caucasus Copper Limited Company between 1905 and 1928, revised and commissioned by Etibank in 1936, and ceased operations 75 years ago. Soil and plant samples (needles of Scotch pine, Pinus sylvestris L.) were collected from five specific regions around the mine and the levels of potentially toxic elements (PTEs) were determined, including As, Zn, Pb, Cd, Ni, Mn, Cr, Cu, Al, and Fe. The data obtained were used to calculate the enrichment factor (EF), geo-accumulation index (Igeo), contamination factor (CF), ecological risk index (ERI), human health risk index (BCF), and plant enrichment factor (EFPlant). In soil samples, the average EF values of certain elements such as As (453), Cu (59.9), Pb (30.7), Zn (5.26) were detected at high levels. However, average Igeo values indicate high pollution levels for As (8.25), Cd (6.72), Cu (4.94), Pb (4.33) and Zn (2.42), indicating the existence of serious ecological risks in the affected areas. Additionally, the average CF values indicate serious pollution levels from heavy metals such as As (1605), Cd (584), Pb (99.4), Cu (81.9), and Zn (14.6), highlighting the extensive pollution situation resulting from mining activities. Meanwhile, average ERI values indicate that Cd, As, Cu, and Pb pose serious ecological risks in the study areas.These PTEs were found in high concentrations in the waste tail and dump. Furthermore, the analysis determined that there was enrichment for Mn, Cd, Al, Cu, Pb, and Fe elements in plant samples. These PTEs have the potential to spread more widely depending on seasonal conditions and local topography. This situation demonstrates the need to measure metal and metalloids concentrations at certain times, taking into account the potential for environmental pollution of surface runoff water and underground resources in areas with high drainage potential from acid mines, such as at the Kuvarshan mine tailings site.
Keywords: 13. Climate action; 11. Sustainability; 6. Clean water; 12. Responsible consumption; 3. Good health